The role of NAD metabolism in neuronal differentiation. (October 2022) - Neves, Diogo; Goodfellow, Brian J.; Vieira, Sandra I.; Silva, Raquel M.
Abstract: Background: Nicotinamide adenine dinucleotide (NAD) metabolism is involved in redox and non-redox reactions that regulate several processes including differentiation of cells of different origins. Here, the role of NAD metabolism in neuronal differentiation, which remains elusive so far, was investigated. Material and methods: A protein-protein interaction network between neurotrophin signaling and NAD metabolic pathways was built. Expression of NAD biosynthetic enzymes in SH-SY5Y cells during retinoic acid (RA)/brain derived neurotrophic factor (BDNF) differentiation, was evaluated. The effects of NAD biosynthetic enzymes QPRT and NAPRT inhibition in neurite outgrowth, cell viability, NAD availability and histone deacetylase (HDAC) activity, were analyzed in RA- and BDNF-differentiated cells. Results: Bioinformatics analysis revealed the interaction between NAD biosynthetic enzyme NMNAT1 and NTRK2, a receptor activated by RA/BDNF sequential treatment. Differences were found in the expression of NAD biosynthetic enzymes during neuronal differentiation, namely, increased QPRT gene expression along the course of RA/BDNF treatment and NAPRT protein expression after a 5-day treatment with RA. QPRT inhibition in BDNF-differentiated SH-SY5Y cells resulted in less neuritic length per cell, decreased expression of the neuronal marker β-III Tubulin and also decreased NAD + levels and HDAC activity. NAPRT inhibition had no effect in neuritic length per cell, NAD + levels and HDAC activity. Of note, NAD supplementation along with RA, but not with BDNF, resulted in considerable cell death. Conclusions: Taken together, our results show the involvement of NAD metabolism in neuronal differentiation, specifically, the importance of QPRT-mediated NAD biosynthesis in BDNF-associated SH-SY5Y differentiation and suggest additional roles for NAPRT beyond NAD production in RA-differentiated cells. Highlights: Understanding neuronal differentiation is crucial for the development of novel therapies to treat several neuropathologies. The expression of NAD biosynthetic enzymes is altered following RA/BDNF-induced SH-SY5Y cells differentiation. NAPRT may have a role beyond NAD production in RA-induced SH-SY5Y differentiation. The de novo route for NAD biosynthesis ensures adequate NAD levels following BDNF-mediated SH-SY5Y differentiation.